HUBUNGAN PENGETAHUAN IBU DENGAN TINDAKAN SIRKUMSISI PADA BAYI PEREMPUAN DI KLINIK CITRA BUNDA TAHUN 2023 - Nababan, Tiarnida; Riskiyani, Nisa Dewi; Nurmala, Nurmala; Nurlia, Nurlia; Nurlela, Nurlela; Hasibuan, Nuri Azri (Universitas Pahlawan, 2024)
Knowledge can be interpreted as the result of the process of knowing that occurs after someone perceives that they have obtained an object. Female circumcision is carried out by cutting the skin on the front of the clitoris without damaging the area. This is considered a human rights violation by the UN and WHO because it does not have a strong medical basis. The aim is to find out whether maternal knowledge is related to the decision to carry out circumcision procedures on baby girls at the Citra Bunda Clinic. This research uses quantitative methods with an analytical survey plan and cross-sectional methods. The subjects of this research were 30 mothers who had daughters aged 0 to 59 months. Based on the results of the Asymp chi-square test. Sig (two-sided) is 0.081. The findings show that there is no significant relationship between female circumcision and the mother's level of understanding, with an error rate of ? = 0.05.